The Effect of Chitosan Dosage Againts Liquid Waste Water Color on "Oriens Handicraft" Sasirangan Home Industry, Landasan Ulin - Arifin Arifin; Ayu Karlina; Abdul Khair (Journal of Health Science and Prevention, 2017)
The growth of sasirangan fabricated prodution has brought positive impact on the welfare of Banjarnese people.Â On the other hand, it also have negative impacts in the form environmental pollution as a result of sasirangan industrial liquid waste disposal without any proper treatment proccess. This study aims to determine the effect of chitosan dosage againts liquid waste water color on "Oriens Handicraft" sasirangan home industry. This is an experimental study, the test was conducted in the chemistry laboratory of environmental health department while the color level examination conducted at the Banjarbaru Industrial Standardization and Research Center. One way anova test with Î± = 0,05% was used for analyzed the data while chitosan regression statistic test with 84% deacetylation degree can be utilized as coagulant material for environmentally friendly sasirangan wastewater treatment with dose variation from 600, 650,700, 750 untill to 800 mg / lt. The highest color concentration eduction occurred at 750 mg / lt doses with 50,5% reduction and the lowest control at 650 mg/lt dose by 43%. The results showed that there were significant differences between color level and chitosan dose. Therefore, the government needs to play a significant role in sasirangan liquid waste treatment by using natural and environmentally friendly coagulant materials such as chitosan.